2012
DOI: 10.1074/jbc.m111.295451
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Promotes β-Amyloid Trafficking and Degradation by Modulating Microglial Cholesterol Levels

Abstract: Background: Intracellular A␤ degradation is enhanced in the presence of apoE. Results: Lowering cellular cholesterol levels facilitates intracellular trafficking of A␤ to lysosomes and enhances its degradation. Conversely, increasing cholesterol levels retards the delivery and inhibits degradation of A␤. Conclusion:The cholesterol efflux function of apoE mediates its ability to promote A␤ degradation. Significance: We demonstrate a direct role for cholesterol in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 86 publications
3
129
0
2
Order By: Relevance
“…ApoE has been shown to be essential for efficient A degradation via microglia by neprilysin or in the extracellular milieu by insulin degrading enzymes (87). More importantly, this process is dependent on the lipidation status of APOE, suggesting that apoE exerts its effects via manipulation of cellular cholesterol levels (87,140). More recently, the newly discovered AD risk gene that encodes the triggering receptor expressed on myeloid cells 2 (TREM2) (141,142) protein was found to have apoE as one of its ligands (143,144).…”
Section: Apoe and Cellular Metabolism Of Amentioning
confidence: 99%
“…ApoE has been shown to be essential for efficient A degradation via microglia by neprilysin or in the extracellular milieu by insulin degrading enzymes (87). More importantly, this process is dependent on the lipidation status of APOE, suggesting that apoE exerts its effects via manipulation of cellular cholesterol levels (87,140). More recently, the newly discovered AD risk gene that encodes the triggering receptor expressed on myeloid cells 2 (TREM2) (141,142) protein was found to have apoE as one of its ligands (143,144).…”
Section: Apoe and Cellular Metabolism Of Amentioning
confidence: 99%
“…Among these, ApoE is known to participate in Aβ production, aggregation, and clearance in an isoform-dependent manner 83,84 . Cholesterol levels in the brain can affect Aβ synthesis, clearance and neurotoxicity.…”
mentioning
confidence: 99%
“…Previous groups demonstrated that reduced plasma cholesterol in neuronal membranes favors the production of nonamyloidogenic Aβ peptides by α‐secretase and lysosomal degradation of amyloidogenic Aβ peptides in microglia. In contrast, increased cholesterol levels in neuronal membranes increased presenilin and BACE activities favoring amyloidogenic Aβ production and inhibited microglial lysosomal degradation of amyloidogenic Aβ peptides 33, 34. It is also possible that increased cholesterol accumulation in brain endothelial cells due to reduced efflux can impair the flux of Aβ into and from the nervous system; however, this pathway has not been investigated.…”
Section: Discussionmentioning
confidence: 99%